(untitled) (IUS LAW Journal, 2025)
This study aims to show the impact of the United States of America (the US) sanctions on international relations, principles of international law, and the countries targeted and not targeted by sanctions. Since sanctions are not issued by a legislative authority of the international community, which constitutes a clear violation of the principles of international law, they may lead to the US having an impact on those countries and issuing potential questions of neocolonialism. Also, they can lead to creating alliances between countries that support sanctions and others that reject them, which may result in the collapse of world peace. The effects of the US sanctions go beyond the principles of personality and territoriality of law and affect the sovereign states recognized in international law, as well as the global economic and social system, and the rights of peoples in the sanctioned countries. These sanctions may question the legal principle that there is no crime or punishment without law.